The Lotterys plus one - Donoghue, Emma, 1969- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Once upon a time, two couples with Jamaican, Mohawk, Indian, and Scottish ethnic roots won the lottery and bought a big house where all of them, four adults and seven adopted and biological children, could live together in harmony--but change is inevitable, especially when a disagreeable grandfather comes to stay.